2021
DOI: 10.1111/geb.13296
|View full text |Cite
|
Sign up to set email alerts
|

CarniDIET 1.0: A database of terrestrial carnivorous mammal diets

Abstract: Motivation A species’ diet is central to understanding many aspects of its biology, including its behaviour, movement, and ecological niche. The diets of terrestrial carnivorous mammals, defined here as species primarily consuming other mammals (hereafter, mammal‐consumers), have been extensively studied and can vary in the proportion of different food types, and species, consumed across their geographic ranges. Accessibility to data capturing such variation in diets of mammal‐consumers across the variety of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…For example, expressing diet as percentage of item consumption is definitely an improvement compared with coarse diet categories, but still ignores that in some species diet can vary substantially across habitats. For example, the CarniDIET database (Middleton et al., 2021) contains several locally recorded diets for >100 species of carnivores, therefore allowing assessment of how local prey availability and diversity can influence predator population densities. Furthermore, life‐history traits (e.g., litter size and sexual maturity age) and social (e.g., group size), reproductive (e.g., monogamy vs. polygamy) and territorial behaviour are unexplored factors that might also explain why some taxa tend to deviate substantially from model predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, expressing diet as percentage of item consumption is definitely an improvement compared with coarse diet categories, but still ignores that in some species diet can vary substantially across habitats. For example, the CarniDIET database (Middleton et al., 2021) contains several locally recorded diets for >100 species of carnivores, therefore allowing assessment of how local prey availability and diversity can influence predator population densities. Furthermore, life‐history traits (e.g., litter size and sexual maturity age) and social (e.g., group size), reproductive (e.g., monogamy vs. polygamy) and territorial behaviour are unexplored factors that might also explain why some taxa tend to deviate substantially from model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expressing diet as percentage of item consumption is definitely an improvement compared with coarse diet categories, but still ignores that in some species diet can vary substantially across habitats. For example, the CarniDIET database (Middleton et al, 2021) This study provides a comparative overview of population densities in terrestrial mammals that can find applications in many ecology and conservation studies. The quality of our estimates is contingent on the data available and, as more data are collected, we will be able to provide more accurate and reliable predictions of species population density.…”
Section: Caveats and Future Research Linesmentioning
confidence: 99%
“…Importance of observed prey items for cougars and gray wolves were derived from CarniDIET [33]. We only included studies that reported the frequency of a prey item across predator scats in a study.…”
Section: Theoretical Predator Prey Rangesmentioning
confidence: 99%
“…Despite major improvements in the consolidation and accessibility of trait data, there is not yet a single-source centralised database spanning behaviour, physiology, habitat, and other trait data for a wide range of species. Existing databases are often linked by taxonomy ( e.g., FishBase (Froese & Pauly, 2010), CoralTraits (Madin et al, 2016), MammalBase (Lintulaakso, 2013), AmphiBio (Oliveira, São-Pedro, Santos-Barrera, Penone, & Costa, 2017)); trait type ( e.g., TreeOfSex (The Tree of Sex Consortium 2014), TreeBase (Boettiger & Temple Lang, 2012), Xylum Functional Traits (Borghetti, Gentilesca, Colangelo, Ripullone, & Rita, 2020)); data type ( e.g., GBIF (https://www.gbif.org/), MOL (Jetz, Thomas, Joy, Hartmann, & Mooers, 2012), TetraDensity (Santini, Isaac, & Ficetola, 2018)); or a combination of the taxonomies and traits (WooDiv (Monnet et al, 2021), CarniDiet (Middleton, Svensson, Scharlemann, Faurby, & Sandom, 2021)). A number of other databases take a more general approach in their thematic scope, but are still constrained to a limited set of traits and taxonomy ( e.g., Amniote (Myhrvold et al, 2015), Pantheria (Jones et al, 2009), BIEN (Enquist, Condit, Peet, Schildhauer, & Thiers, 2016; Maitner et al, 2018), TRY (Kattge et al, 2020)).…”
Section: Introductionmentioning
confidence: 99%